STUDY OF INSOMNIA AT PRECLINICAL AND CLINICAL STUDENTS, FACULTY OF MEDICINE - Pramudita Probosiwi; Rihadini -; Kanti Ratnaningrum (Universitas Muhammadiyah Semarang, 2017)
Insomnia is one of sleep disorder. Prevalence of insomnia in health students group is higher than nonhealth students group. This study aims to compare of insomnia level at preclinical and clinical students faculty of medicine. A cross sectional study was conducted on medical students, Faculty of Medicine, University of Muhammadiyah Semarang (Unimus). Determination of sample using Slovin formula withsimple random sampling technique. students did not have problems such as had stopped in the previous semester, college not because of his wishes, was not being sad condition, and not smoking were included in study. Insomnia level was measured using Insomnia Severity Index (ISI questionnaire) and analyzed using chi-square test. Among 86 samples divided into 2 groups (preclinical and clinical stage), there is a significant difference insomnia level (p = 0.006) at preclinical and clinical students. Insomnia level ofclinical students is higher than preclinical students in Faculty of Medicine. Keywords : insomnia, preclinical student, clinical student